Parenting Styles of Fishermen and Female Migrant Workers (TKW) Families in Instilling Religious Characters for the Children’s - Nailul Ghufron Aziz (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2020)
This study aims to determine the types of parenting for the families of fishermen and Female Migrant Workers (TKW) as well as the driving and inhibiting factors in the formation of religious character in children. This research is a field research using a qualitative approach. The data in this study were obtained through interviews, observation, and documentation. The results of this study indicate that: First, the parenting styles used by several mothers in fishermen families are authoritarian, militaristic, democratic, purposeful, and paternalistic. The parenting styles used by fathers in TKW families are role-transfer, laissez-faire, transactional, and affiliation. Second, there are several driving and inhibiting factors in the formation of religious character in children. These factors are the structure of the physical environment, social environment, educational environment, psychological atmosphere in the family, socio-culture in the family, and parental control of their children. The success of these factors is influenced by parent’s attention. Parents who care about their children tend to have success in all elements of environmental structures. On the other hand, parents who are indifferent to their families tend to fail in all elements of structures.